IMPLEMENTATION SERVICES INFORMATION TO OVERCOME THE FAILURE OF LEARNING - SUKATNO SUKATNO (Universitas Muhammadiyah Tapanuli Selatan, 2018)
This study is based on problems that Many students who can not achieve the learning outcomes as expected by the educators in this case a failure in learning. The research goal is to describe the failure of student learning before and after the given service information, and determine the effectiveness of the implementation of information services in addressing the failure to learn. The method used in this research is True experimental design with pretest form-Posttest Control Group Design. With a sample of experimental class is class XI-TITL one of 25 students and the control class is class XI-TITL2 many as 22 students so as the total sample of 47 students. Data were analyzed using the Wilcoxon rank test signesd and Kolmogorov Smirnov 2 with the help SPPSS version 20.00. The results obtained in the experimental group of researchers pretest posttest 94.3 and 99.6 and the control group pretest posttest 87.3 and 93.7. Test the hypothesis produce the experimental group Z on pretest-posttest with values -3,727b and signed pretest-posttest worth 0.00, whereas in the control group pretest-posttest Z on the value -3,232b and signed pretest-posttest berniai 0.01. At posttest and posttest control experiments signed (2-tailed) 849 experimental group and the control group 940, while the average veriabel the experimental group 93.7273 99.6800 in the control group. The conclusion is that the researchers obtained the experimental group was higher than the control group. Keywords: Information Services, Overcoming Failure Study